Acute Respiratory Distress Syndrome: Etiology, Pathogenesis, and Summary on Management. (August 2020) - Kaku, Shawn; Nguyen, Christopher D.; Htet, Natalie N.; Tutera, Dominic; Barr, Juliana; Paintal, Harman S.; Kuschner, Ware G.
The acute respiratory distress syndrome (ARDS) has multiple causes and is characterized by acute lung inflammation and increased pulmonary vascular permeability, leading to hypoxemic respiratory failure and bilateral pulmonary radiographic opacities. The acute respiratory distress syndrome is associated with substantial morbidity and mortality, and effective treatment strategies are limited. This review presents the current state of the literature regarding the etiology, pathogenesis, and management strategies for ARDS.